Leverage, Ukuran Dewan Komisaris, Ukuran Dewan Pengawas Syariah dan Pengaruhnya Terhadap Pengungkapan Islamic Social Reporting (ISR) - Murdiansyah, Isnan (MALIA: Journal of Islamic Banking and Finance, 2021)
The purpose of this research is to find out the influence of leverage, size of the board of commissioners and sharia supervisory board toward the disclosure of Islamic Social Reporting (ISR) at Sharia Commercial Bank in Indonesia during 2017-2019 and test it. Purposing sampling is the technique that been used in this research with the samples 12 Sharia Commercial Bank during 3 years observation respectively with the result obtained 36 samples. The analysis technique used in this research was multiple regressions. The analysis result shows that leverage has no significant influenced toward the disclosure of Islamic Social Reporting (ISR), size of the board of commissioners has a positive significant influenced toward the disclosure of Islamic Social Reporting (ISR) and syaria supervisory board has no significant influenced toward the disclosure of Islamic Social Reporting (ISR).